Successful open fetal resection of a pericardial teratoma: A case report - Bailey D. Lyttle; Alyssa E. Vaughn; Lauren T. Gallagher; James Jaggers; Henry L. Galan; Kenneth W. Liechty; S. Christopher Derderian (Elsevier, 2023)
Introduction: Pericardial teratomas are rare mediastinal tumors that can lead to pericardial effusions with subsequent tamponade physiology and progression to hydrops. While overall outcomes can be favorable, prognosis is poor in the setting of hydrops, particularly at an early gestational age. Case presentation: We present a case in which a 29-year-old female presented at 26 3/7 weeks' gestation carrying a fetus with a prenatally diagnosed pericardial teratoma. During a period of outpatient monitoring with twice-weekly ultrasounds and echocardiograms, the fetus developed a rapidly expanding pericardial effusion with cardiac compromise, prompting admission. Following admission, the fetus developed early signs of hydrops including ascites and pulmonary effusions at 27 6/7 weeks, and after a multidisciplinary discussion underwent open fetal resection two days later. This resulted in the resolution of hydrops with delivery at 29 3/7 weeks and ultimately neonatal survival without the need for any additional postnatal procedures. Conclusion: In this case report, we discuss current fetal interventions utilized in the management of pericardial teratomas, including the few prior attempts at open fetal resection. We also highlight the potential benefit of open fetal resection in the setting of early hydrops to optimize further in-utero development while simultaneously addressing the tamponade physiology of pericardial teratomas that can lead to hydrops and fetal demise. Here, we demonstrate that open fetal resection is a feasible and effective treatment option for carefully selected patients with pericardial teratomas, particularly in the setting of early hydrops.